The COVID-19 pandemic and graduation in visual arts: collaborative experiences in remote teaching - Pianowski , Fabiane; Rache , Rita Patta; de Azevedo , Cláudio Tarouco (Seven Editora, 2023)
Since the beginning of the COVID-19 pandemic in 2020, universities have suspended in-person activities, and, after a series of measures education has become remote. In this context, the Visual Arts Majors at FURG - Bachelor and Licentiate - in a joint action between the Coordination, Structuring Faculty Nucleus (NDE), professors, and students - prepared an Emergency Pedagogical Project (EPP), whose pedagogical proposals are structured in teaching-research-extension projects and interdisciplinary modules. We present this process, the challenges, and the solutions built, discussing the role of Public University and Visual Arts undergraduate courses in this moment of sanitary and political crisis. DOI: https://doi.org/10.56238/devopinterscie-064